Dry or wet? What is the best choice to determine gonadosomatic and hepatosomatic indexes in females of Macrobrachium amazonicum? - Paschoal, Lucas Rezende Penido [UNESP]; de Oliveira, Leo Jaime Filgueira [UNESP]; Andrioli, Guilherme Casemiro [UNESP]; Zara, Fernando José [UNESP] (Hindawi, 2019)
The gonadosomatic (GSI) and hepatosomatic (HSI) indexes are widely used for the evaluation of reproductive biology in crustaceans. However, the use of either wet or dry weight for estimating these indexes is not standardized in the literature. Here, we compare the GSI and HSI indexes based on wet and dry samples of females of Macrobrachium amazonicum from populations with different phenotypes (large and small-size prawns) as a model. In our analysis, for GSI, the application of wet weight tended to overestimate the values recorded in the initial (I-II) and intermediate (III) stages of ovarian development, and underestimate the results in the final (IV-V) stages when compared to the use of dry weight. This could be attributed to the reduction in cytoplasmic organelles and water content of the cytosol due to the increase in yolk and lipids in the oocytes throughout ovarian development. For HSI, no significant differences were detected between wet and dry samples. However, the dry HSI computed at all stages of development was overestimated when compared to the use of wet samples, and only the hepatopancreas of females at the final stage (V) showed a significant decrease in water content. Thus, our results indicate that M. amazonicum females maintain constant hepatopancreatic reserves throughout ovarian development. In this way, the use of dry weight is more adequate to estimate GSI and HSI in this species.
Keywords: Amazon River prawn; Caridea; hepatopancreas; intracell water; lipid reserves; ovary